2021
DOI: 10.3390/ph14040304
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antiviral Activity against HSV-1 and SARS-CoV-2 by Antimicrobial Peptoids

Abstract: Viral infections, such as those caused by Herpes Simplex Virus-1 (HSV-1) and SARS-CoV-2, affect millions of people each year. However, there are few antiviral drugs that can effectively treat these infections. The standard approach in the development of antiviral drugs involves the identification of a unique viral target, followed by the design of an agent that addresses that target. Antimicrobial peptides (AMPs) represent a novel source of potential antiviral drugs. AMPs have been shown to inactivate numerous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 50 publications
3
58
1
Order By: Relevance
“…No difference in viral titers of treated and control samples was observed, indicating that the compound did not exert intrinsic virucidal activity (Figure S7). This finding contrasted with many reports in the literature in which natural peptides showed direct inactivation of HSV particles by disrupting the viral envelope [37][38][39][40][41].…”
Section: Investigation Of A-3302-b Mechanism Of Actioncontrasting
confidence: 99%
“…No difference in viral titers of treated and control samples was observed, indicating that the compound did not exert intrinsic virucidal activity (Figure S7). This finding contrasted with many reports in the literature in which natural peptides showed direct inactivation of HSV particles by disrupting the viral envelope [37][38][39][40][41].…”
Section: Investigation Of A-3302-b Mechanism Of Actioncontrasting
confidence: 99%
“…Depending on the action mechanism, recent studies have claimed that LL37, along with inactivating HSV-1, can be used as a therapeutic agent against SARS-CoV-2 [ 24 ]. Additionally, a new study found that LL37 attaches to the SARS-CoV-2 spike protein [ 25 ] instead of just attaching itself to the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed thermodynamics analyses, both experimental and computational are needed to clarify this point. Nevertheless, our work and that of others suggests that design of AMP-derived peptides and peptide mimetics could be a useful strategy in combating CoV-2 variants (Bakovic et al, 2021;Diamond et al, 2021;Zhang et al, 2021).…”
Section: Articlementioning
confidence: 77%